Formation of an RNA Heterodimer upon Heating of Nodavirus Particles - Krishna, Neel K. (American Society for Microbiology, 1999)
Flock House virus is a small icosahedral insect virus of the family Nodaviridae. Its genome consists of two positive-sense RNA molecules, which are believed to be encapsidated into a single viral particle. However, evidence to support this claim is circumstantial. Here we demonstrate that exposure of nodavirus particles to heat causes the two strands of viral RNA to form a stable complex, directly establishing that both RNAs are copackaged into one virion. The physical properties of the RNA complex, the effect of heat on the particles per se, and the possible relevance of these findings to the nodavirus life cycle are presented.